Covid-19 Pandemic and Human Rights – Myth or Reality? - Tvrdoň, Miroslav; Akimjak, Amantius; Slobodova Novakova , Katarina; Biryukova, Yulia Nickolaevna (Journal of Education Culture and Society, 2022)
Aim. During the pandemic situation of Covid-19, various true or false information about the spread, treatment, prevention, and vaccination against Covid-19 began to spread in the media, as well as in the real world. It is necessary to fight against various hoaxes on the basis of modern and especially scientifically documented information.Method. This study addresses human rights and change in society before and during the Covid-19 pandemic situation. The authors of the study worked with specific texts and with the help of literary and textual analysis, as well as analytical and synthetic methods. Basic human rights and freedoms during the pandemic were pointed out, together with various myths which circulate among non-professional individualsResults. The results of the study confirm that the pandemic situation of Covid-19 requires constant explanation, exploration, and confirmation of professional and scientific studies by experts in the media as well as within the social life of people, just to reject various hypotheses of people who are not experts in the field and who disseminate false and scientifically and technically unsubstantiated information.